Phytochemical Screening and Evaluation of Biological Activities of Some Medicinal Plants of Phagwara, Punjab - Arora Chugh, Charu; Mehta, Sanjeev; Dua, Heena (Asian Journal of Chemistry, 2012)
In the present work, phytochemical screening of 12 medicinal plant species namely Ocimum sanctum, Psoralea corylifolia, Crotolarea juncea, Sansevieria ghiana, Gossypium herbaceum, Schleichera oleosa, Anethum sowa, Analrograplis panicculata, Punica granatum, Argemone mexicana, Gmelina arborea and Prunella vulgaris has been carried out. Saponins isolated from O. sanctum and A. mexicana have shown excellent antibacterial potential against E. coli with inhibition zone of 30 and 28 mm respectively. Alkaloids from P. corylifolia, G. herbaceum, S. oleosa, S. ghiana, P. granatum and C. juncea possess potential activity against E. coli. Flavonoids of O. sanctum, P. corylifolia and P. granatum possess significant potential against E. coli. These studies will be helpful in developing plant based antimicrobial formulations, which are expected to be superior to synthetic antimicrobial drugs and formulations.